Compact linear accelerator integrated with a high-power microwave source - Zi-Jing Zhang; Weihao Liu; Hongliang Xu (Physical Review Accelerators and Beams, 2025)
Particle accelerators have played a pivotal role in scientific research, medical applications, and industrial processes. However, conventional radio-frequency accelerators face limitations due to their large size, high cost, and dependence on external microwave sources. This paper presents a novel linear accelerator design that integrates a high-power microwave source directly into the accelerator structure, eliminating the need for external drivers and enabling a more compact, cost-effective, and simplified system. The proposed design employs an X-band backward wave oscillator driven by a 50 keV hollow continuous electron beam. The generated microwave power is coupled into a central X-band standing-wave acceleration structure via a radial coupler. Simulations demonstrate that a witness beam passing through this structure can be accelerated from 50 keV to over 4 MeV across 10 acceleration cells. This work serves as a foundational study on integrated accelerator concepts, offering a pathway toward more efficient, scalable, and versatile particle acceleration systems.